Dinamika Hukum Perdata Internasional dalam Pengakuan Pernikahan WNI di Luar Negeri - Laila Anggraini, Fita; Kusumawati, Diana; Ghalidza Adhevi, Muhammad; Mul Erowati, Eti (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
In the era of globalization, inter-country marriages are increasingly common, including among Indonesian citizens (WNI) who choose to marry abroad. However, the recognition and validity of such marriages in Indonesia is a complex legal challenge. This article aims to explore the dynamics of International Private Law in the context of recognizing Indonesian citizens' marriages abroad, as well as identifying the legal challenges faced and solutions that can be implemented to increase legal certainty and protect the rights of Indonesian citizens. The research method used is qualitative with a descriptive analytical approach, utilizing secondary data sources such as legal literature, regulatory documents and case studies. The research results show that the marriage recognition mechanism involves a complicated administrative process, including registration at the Indonesian representative office and legalization of documents. Challenges faced include differences in legalization procedures between countries and a lack of information regarding the steps that must be taken. To increase legal certainty, it is recommended that regulations be harmonized, increase legal dissemination, and use digital technology in the marriage recognition process. It is hoped that this research can provide useful policy recommendations for protecting the rights of Indonesian citizens who marry abroad.